Prenatal finding of isolated ventricular septal defect: genetic association, outcomes and counseling - Chen, Xin; Zhang, Qian; Lu, Man; Feng, Qiuxia; Qin, Litao; Liao, Shixiu (Frontiers in Genetics, 2024)
The innovation in ultrasound has greatly promoted the prenatal diagnosis of ventricular septal defect. As a minor lesion of congenital heart disease, the prenatal genetic counseling of isolated ventricular septal defect faces some challenges, including the true genetic correlationship, selection of appropriated testing methods to identify deleterious mutations, and avoidance of overdiagnosis and overintervention. Researchers have explored the prenatal diagnosis efficiency of commonly used cytogenetic and molecular genetic technologies. Small insertions/deletions and monogenic variants with phenotypic heterogeneity play important role and contribute to the comprehend of pathogenesis. Isolated ventricular septal defect fetuses without genetic finding and extracardiac structural abnormality generally have good pregnancy outcome. Long-term follow-up data is needed to describe the comprehensive map, such as the potential missed diagnosis especially late-onset syndromes, the impact on the quality of life and life expectancy. When conducting prenatal genetic counseling, strict adherence to ethical principles is needed to ensure that the rights of all parties involved are fully protected. Clinicians should carefully evaluate the risks and benefits and provide parents with sufficient information and advice to enable them to make informed decisions.